Experimental results on sound absorption coefficients of Malaysian woods - Mohammad, Janatul Islah; Johari, Norhasnira; Said, Md. Radzai; Mohd. Nor, Mohd. Jailani (2011)
Sound absorption coefficient is an important parameter to calculate the reverberation time of an enclosure. There are published data inside text books on the sound absorption coefficients of typical materials, such as concrete, carpet, drapes, etc. However, the sound absorption coefficients of Malaysian wood have not been published to date. These woods are divided into four different categories, which are heavy hardwoods, medium hardwoods, light hardwoods and softwoods. This paper presents preliminary results of the sound absorption coefficients of two types of Malaysian woods: Balau (Shorea spp) and Nyatoh (Species of Sapotaceae); based on the transfer function method using the impedance tube. A bigger tube (100 mm) is used for measuring the sound absorption coefficients at lower frequencies (below 800 Hz) and a smaller tube (28 mm) is used for measuring the sound absorption coefficients at higher frequencies (above 800 Hz). It is found that the sample with the highest sound absorption coefficient is 18 mm Balau (higher density) while the lowest is the 34 mm Nyatoh (lower density) without the presence of air gaps. With variation of air gaps present, Nyatoh shows the more substantial results in comparison with Balau whereby the absorption coefficient are significantly higher than the ones without air gaps. However, the overall absorption coefficient remains low (below 0.2) at all frequencies, regardless having different thickness, density and variation of air gaps of up to 3”